2013
DOI: 10.1177/0829573512468846
|View full text |Cite
|
Sign up to set email alerts
|

Self-Stigma of Mental Illness in High School Youth

Abstract: Despite the prevalence of mental health problems, society continues to stigmatize and discriminate against people with mental illness and in particular, schizophrenia. Among the negative consequences of stigma, is that some individuals with mental illness internalize negative stereotypes about themselves, referred to as self-stigma, which is associated with a reluctance to seek needed treatment. The challenge to overcome mental illness stigma has led to the development of global anti-stigma initiatives, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
(73 reference statements)
2
25
1
Order By: Relevance
“…The observed improvement in participants' knowledge accords with other research, which has demonstrated that peer education training can lead to positive changes in peer educators' knowledge about particular health behaviours (Badura et al, 2000;Haignere et al, 1997). These results are encouraging given self-stigma has been shown to be a key obstacle to seeking help for mental health concerns among young people in the general population and that many young people do not have appropriate mental health knowledge (Dooley & Fitzgerald, 2012;Gulliver et al, 2010;Hartman et al, 2013;Rose et al, Downloaded by [University of Lethbridge] at 11:07 11 June 2016youngMinds, 2010). Thus, peer-based approaches to mental health promotion may be an effective way of engaging young people in conversations about mental health and changing their beliefs about help-seeking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed improvement in participants' knowledge accords with other research, which has demonstrated that peer education training can lead to positive changes in peer educators' knowledge about particular health behaviours (Badura et al, 2000;Haignere et al, 1997). These results are encouraging given self-stigma has been shown to be a key obstacle to seeking help for mental health concerns among young people in the general population and that many young people do not have appropriate mental health knowledge (Dooley & Fitzgerald, 2012;Gulliver et al, 2010;Hartman et al, 2013;Rose et al, Downloaded by [University of Lethbridge] at 11:07 11 June 2016youngMinds, 2010). Thus, peer-based approaches to mental health promotion may be an effective way of engaging young people in conversations about mental health and changing their beliefs about help-seeking.…”
Section: Discussionsupporting
confidence: 87%
“…Unfortunately, research has shown many young people have a lack of knowledge about mental health and this can negatively stigmatize mental health (Rose, Thornicroft, Pinfold, & Kassam, 2007;youngMinds, 2010). Furthermore, studies have indicated that negative beliefs about seeking help for mental health concerns is a key barrier to accessing support among young people from the general population (Gulliver, Griffiths, & Christensen, 2010;Hartman et al, 2013). It is important to address these beliefs, as research has indicated that young people who share their problems have lower levels of psychological distress (Dooley & Fitzgerald, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Participants also completed two scales that assess constructs known to be associated with reduced self‐reported mental illness stigma, including familiarity with mental illness (Couture & Penn, ; Holmes, Corrigan, Williams, Canar, & Kubiak, ) and social desirability bias (e.g., Hartman et al., ; Stier & Hinshaw, ).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive investigation of the prevalence of self‐stigma among adolescents has yet to be conducted, and it is arguably the case that the relevance of self‐stigma among students struggling with mental health problems remains underappreciated and underrecognized. An initial study found that at least one in eight high school students scored in the range of those who report self‐stigma about seeking help for mental health concerns (Hartman et al, ). Hartman et al () examined whether a single session could lower stigma and self‐stigma in high school youth ranging from grades 9 through 12.…”
Section: Introductionmentioning
confidence: 99%
“…An initial study found that at least one in eight high school students scored in the range of those who report self‐stigma about seeking help for mental health concerns (Hartman et al, ). Hartman et al () examined whether a single session could lower stigma and self‐stigma in high school youth ranging from grades 9 through 12. They were shown an interactive presentation on the topic of mental illness, including an autobiographical talk by a woman with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%